The FiO2 is associated with the successful extubation of mechanically ventilated neonates - Shepherd EG; Alexander LJ; Kuehne B; Reber KM; Nelin LD (Research and Reports in Neonatology, 2011)
Edward G Shepherd1, Lori J Alexander2, Brandon Kuehne2, Kristina M Reber1, Leif D Nelin1,31Department of Pediatrics, The Ohio State University, Columbus, OH, USA; 2Neonatal Respiratory Therapy, Nationwide Children's Hospital, Columbus, OH, USA; 3Center for Perinatal Research, Research Institute at Nationwide Children's Hospital, Columbus, OH, USAAbstract: Early extubation may be beneficial in preventing or attenuating the development of bronchopulmonary dysplasia (BPD). We tested the hypothesis that patients extubated from higher ventilator pressures would be more likely to fail extubation. To determine the relationship between peak inspiratory pressure (PIP), positive end expiratory pressure (PEEP), and fraction of inspired oxygen (FiO2) at the time of extubation and success of extubation, we reviewed the charts of all patients extubated in our neonatal intensive care unit (NICU) over two time periods; April 4, 2005–May 7, 2005 and November 14, 2005–January 7, 2006. Successful extubation was defined as not requiring re-intubation within 36 hours of extubation. There were 67 patients extubated during the study periods, and 58 patients (88%) were successfully extubated. There was no difference in the ventilator settings (PIP, PEEP, mean airway pressure, ventilator rate, or inspiratory time) between the patients with successful vs unsuccessful extubations. However, the FiO2 was significantly (P = 0.011) lower in the successful extubations (median 24, intraquartile range 21–31) than in the unsuccessful extubations (median 33, intraquartile range 28–43). The median PIP was 22 cm H2O (intraquartile range 20–24) in the patients successfully extubated. Our data suggest that the FiO2 may be the only ventilator setting associated with successful extubations in this patient population. Randomized control trials are needed to determine if extubating neonatal patients from relatively high PIP using FiO2 will shorten the duration of mechanical ventilation.Keywords: extubation, neonates, FiO2, bronchopulmonary dysplasia